2019
DOI: 10.1098/rsbl.2018.0607
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte chase behaviours: discrimination between Gram-negative and Gram-positive bacteria by amoebae

Abstract: Phagocytes are cells that pursue, engulf and kill bacteria. They include macrophages and neutrophils of the mammalian immune system, as well as free-living amoebae that hunt and engulf bacteria for food. Phagocytosis can result in diverse outcomes, ranging from sustenance to infection and colonization by either pathogens or beneficial symbionts-and thus, discrimination may be necessary to seek out good bacteria while avoiding bad ones.Here we tested whether the soil amoeba Dictyostelium discoideum can discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Brock et al (2018) found that 81% of culturable symbionts of D. discoideum were edible. The ability of social amoebae to preferentially chemotax toward gram-negative bacteria (Rashidi and Ostrowski, 2019) may also increase the likelihood of potential gram-negative bacterial symbionts being passively transmitted from the environment.…”
Section: Host Factors Affecting Social Amoeba Microbiomesmentioning
confidence: 99%
“…Brock et al (2018) found that 81% of culturable symbionts of D. discoideum were edible. The ability of social amoebae to preferentially chemotax toward gram-negative bacteria (Rashidi and Ostrowski, 2019) may also increase the likelihood of potential gram-negative bacterial symbionts being passively transmitted from the environment.…”
Section: Host Factors Affecting Social Amoeba Microbiomesmentioning
confidence: 99%
“…discoideum had different gene expression profiles when exposed to different bacteria (Benghezal et al., 2006; Lamrabet et al., 2020; Nasser et al., 2013). They were also more attracted to Gram‐negative bacteria in a chemotaxis assay (Rashidi & Ostrowski, 2019). However, it is not clear whether such food preference is determined by bacterial nutrition (greater production of amoeba spores after feeding on a given amount of bacteria).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that D . discoideum prefers Gram‐negative bacteria in a chemotaxis assay (Rashidi & Ostrowski, 2019). This study further shows that D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies involving knockout mutants, unbiased mutational screens, genome-wide transcriptional changes and proteomic analysis during phagocytosis, macropinocytosis or infection have produced a large wealth of data, which have been the subject of several reviews in the last years (Bozzaro and Eichinger, 2011;Dunn et al, 2018;Cardenal-Muñoz et al, 2018;Swart et al, 2018). Among more recent data not yet covered by reviews, it is worth mentioning: (I) evidence that Dictyostelium cells are highly sensitive to bacterial chemoattractants, but phagocytosis per se is independent of chemoreceptor sensing (Meena and Kimmel, 2017); (II) in apparent contrast to this, the characterization of the G protein-coupled, folic acid receptor fAR1, which recognizes the saccharide core of LPS and stimulates gram-negative bacterial phagocytosis, providing a plausible mechanism for the involvement of G proteins in phagocytosis ; discrepancy between both results may be due to the different phagocytosis assays used; (III) evidence that Dictyostelium discriminates between Gram-(-) and Gram-(+) bacteria, migrating preferentially toward Gram-(-) bacteria (Rashidi and Ostrowski, 2019), and that their growth on Gram-(-) or Gram-(+) bacteria elicit different transcriptomic profiles, with some genes essential for growth (Nasser et al, 2013); ((IV) the identification of PIKFyve/FAB1 in controlling acidification of phagosomes (Buckley et al, 2019), thus extending previous studies on the role of phosphoinositides in phagocytosis, macropinocytosis and resistance to pathogens (Swart et al, 2018;Hoeller et al, 2013;Peracino et al, 2010; (V) Similarly, it has been shown that the RasGAP IqgC is a negative regulator of macropinocytosis and large particle phagocytosis (Marinović et al, 2019), strengthening the role of Ras signalling in these processes Junemann et al, 2016;Bolourani et al, 2010; (VI) While bacterial phagocytosis is essential for growth, it has also been shown that during slug stage, cells maintain as endosymbionts bacteria that have been coated with the secreted lectin discoidin I, and that could possibly be used later as a food source (Dinh et al, 2018).…”
Section: Biological Processmentioning
confidence: 99%